Pengaruh Konservatisme Akuntansi Terhadap Penilaian Ekuitas Dengan Good Corporate Governance Sebagai Variabel Pemoderasi (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di PT BEI) - Yona Efri Yenti; Efrizal Syofyan (Universitas Negeri Padang, 2013)
The aim of this study is to examine and analyze the effect of: 1) Accounting Conservatism to Equity Assessment, 2) Ownership of the relationship conservatism managerial ownership accounting by the equity valuation, 3) Number of Board Commissar of Commissioners of the relationship between accounting conservatism with the company's equity valuation Manufacturing Company Registered in PT Indonesia Stock Exchange. The population of this research is all the manufacturing companies listed on the Indonesia Stock Exchange 2006-2010. The results shows that: 1) no effect on accounting conservatism equity valuation company with a level Sig. 0303> 0.05 and a coefficient (β) 0:51 then H1 is rejected, 2) Managerial Ownership is not a moderation variable that can interact accounting conservatism relationship with the company's equity valuation to the level of Sig. 0064> 0.05 and a coefficient (β) -0139 then H2 is rejected, 3) Number of Board Commissar is a moderation variable that can interact accounting conservatism relationship with the company's equity valuation to the level of Sig. 0001 <0.05 and a coefficient (β) then H3 0372 acceptable. Suggestions to the same study, the sample should be broaden not only on one type of industry, but also all the variables of Good Corporate Governance suspected to be moderation variable Keywords : Equity assessment, accounting conservatism, managerial ownership, number of board commissar.